Eficácia de uma biomembrana com proteínas do látex da planta Calotropis procera na cicatrização: uma alternativa no SUS para o tratamento da úlcera plantar associada à hanseníase - Bulegon, Marília de Oliveira Nunes (2024)
The Calotropis procera plant has been associated with several biological activities. Consistent preclinical trials have demonstrated that a polyvinyl alcohol (1%) biomembrane incorporated with Calotropis procera latex proteins (10%), known as BioMemCpLP, is biocompatible and stimulates wound healing in animal models. Dressings for treating plantar ulcers are typically expensive and difficult to access for the affected population. Therefore, this randomized multicenter clinical study aimed to evaluate the efficacy and safety of BioMemCpLP in plantar ulcers associated with leprosy, with the goal of enabling its standardized use by the SUS. Additionally, the effect of BioMemCpLP on keratinocytes and the mechanisms involved in the healing process were investigated in vitro. The efficacy assessment was conducted over 8 weeks, with 23 patients enrolled and a total of 32 ulcers treated. Fifteen patients (22 ulcers) were treated with BioMemCpLP, five patients (5 ulcers) received treatment only with silver sulfadiazine, and the third group, consisting of three patients (5 ulcers), received hydrocolloid treatment. These protocols are routinely used in the outpatient clinics of specialized centers, with dressings being renewed three times a week on alternate days. The ulcers were evaluated weekly, with the healing rate calculated using the measured area each week as the primary outcome, along with the time it took for the ulcer to close, and the influence of clinical characteristics on healing. In vitro proliferation, migration, and adhesion assays were carried out, along with the evaluation of the expression of the molecules involved in these processes, namely E-cadherin and β-catenin, in human keratinocytes (HaCat). Ulcers treated with BioMemCpLP exhibited a greater healing area compared to controls. More than 88% of ulcers treated with BioMemCpLP were completely healed after 8 weeks of treatment, while both control groups achieved only 11.8% (p=0.041) of complete healing. Ulcers treated with BioMemCpLP also healed in less time than those in the control groups. This superior performance was associated solely with the use of BioMemCpLP and was not correlated with age/sex, age/ulcer location, deformity, or whether or not the patient was cured of leprosy. This study demonstrated that latex proteins extracted from Calotropis procera are bioactive in promoting ulcer healing without noticeable side effects. The healing effect can be attributed to the proteins that make up the biomembrane, which stimulate the proliferation, migration, and cellular adhesion of keratinocytes, in addition to promoting the expression of E-cadherin and β-catenin, thus indicating great potential for wound healing.